Insights into the applicability of the R dot approach for reaction mechanism kinetics studies - Periasamy, Vijay; Tade, Moses; Datta, R. (Pergamon, 2012)
An alternate method, which we call as the R dot approach, to obtain the quasi steady state (QSS) rateexpression for linear kinetics mechanisms (both sequential reaction mechanism and mechanisms withparallel pathways) had been recently proposed. This method requires the use of intermediate reactionroutes (IRR’s) to solve for the unknown intermediate species concentrations. In mechanisms wherethere are many choices of IRR’s, it was not clear which one must be chosen so as to obtain the correctrate expression matching with the QSS rate expression. In this work, it is shown that the correct choiceis the one which will make the rate limiting step (RLS) reversibility equal to the overall reversibility.This also provides a condition to check the applicability of the R dot method to a particular linearkinetics mechanism. For a mechanism with non linear kinetics, the R dot method may sometimesprovide unsatisfactory approximations even if the applicability conditions are satisfied. These areillustrated through four mechanism examples.